2017
DOI: 10.1017/s0954422417000087
|View full text |Cite
|
Sign up to set email alerts
|

Current and future strategies for the nutritional management of cardiometabolic complications of androgen deprivation therapy for prostate cancer

Abstract: Androgen deprivation therapy (ADT) is used widely as part of a combined modality for the treatment of prostate cancer. However, ADT has also been associated with the development of cardiometabolic complications that can increase mortality from cardiovascular events. There is emerging evidence to suggest that ADT-related cardiometabolic risk can be mitigated by diet and lifestyle modification. While the clinical focus for a nutritional approach for achieving this effect is unclear, it may depend upon the timely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Many of the men in our study had central adiposity, as measured by waist-to-hip ratio, and with levels of HbA1c indicative of pre-diabetes, all of which could have contributed to metabolic health risks associated with their PCa (Shlomai et al, 2016). While ADTrelated cardiometabolic risk shares several of the components of metabolic syndrome (Di Sebastiano et al, 2018), ADT adverse effects are distinct in that it develops more rapidly and is characterised by an accumulation of subcutaneous adipose tissue and sarcopenia (Turner et al, 2017). This impacts on men's body composition which is characterised by a loss of skeletal muscle and accumulation of body fat (Morote et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many of the men in our study had central adiposity, as measured by waist-to-hip ratio, and with levels of HbA1c indicative of pre-diabetes, all of which could have contributed to metabolic health risks associated with their PCa (Shlomai et al, 2016). While ADTrelated cardiometabolic risk shares several of the components of metabolic syndrome (Di Sebastiano et al, 2018), ADT adverse effects are distinct in that it develops more rapidly and is characterised by an accumulation of subcutaneous adipose tissue and sarcopenia (Turner et al, 2017). This impacts on men's body composition which is characterised by a loss of skeletal muscle and accumulation of body fat (Morote et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown an association between all-cause mortality and ADT in men with PCa (Davis et al, 2015;Keating et al, 2013;O'Farrell et al, 2015). While ADT is highly effective as a component of combined modality therapy, its use, and specifically, the use of gonadotrophin-releasing hormone (GnRH) agonists, has been associated with the development of sarcopenic obesity and cardiometabolic risk factors, including dyslipidaemia, insulin resistance and elements of metabolic syndrome (Collier et al, 2011;Morote et al, 2015;Turner et al, 2017). An association between ADT and increased risk of CVD and mortality has been recognised in multiple studies (Bosco et al, 2014;Nguyen et al, 2011;Weaver et al, 2013;Zhao et al, 2014) but CVD and links with increased mortality remain contentious in clinical practice.…”
mentioning
confidence: 99%
“…As a result, men with PCa are at a heightened risk of frailty, falls and fractures, and early mortality 3 5 6. Further, the decline in body composition is also associated with sarcopenic obesity, leading to increases in cardiometabolic risk factors 45 46. Consequently, investigations into strategies that may improve musculoskeletal health is of critical importance in this population.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that cardiometabolic risk due to ADT can be decreased by diet and lifestyle modification. 59 However, further research is required to comprehend the impact of TRT on cardiometabolic health and to determine the beneficial or harmless dose, route, and duration time of T administration in clinical conditions. Late-onset hypogonadism is linked to hyperglycemia, increased waist circumference, hypertriglyceridemia, hyperlipidemia, as well as diabetes mellitus.…”
Section: Androgens In Cmsmentioning
confidence: 99%